Devising a Social Credit Score for an individual to analyze their propensity to Default Financially - Diptadeep Das, Anish Agarwal (International Journal of Advanced Science and Technology, 2020)
The latest technological and digital advancements have unfolded new directions for the utilization of customer data in financial services. The authors are trying to convey that the borrowers, consciously or not, leave traces of their intentions in the way they respond to certain circumstances. The purpose of this paper is to form a social credit score of people based on their lifestyle choices and trying to establish a relationship on the individual’s propensity to default financially. Customer behavior will be analyzed based on their social and environmental lifestyle choices, and their social media activity. Based on these data, a parallel will be drawn on the individual’s propensity to default financially. These traits will be measured on a Likert Scale of one to seven and multiple regressions will be conducted on these. The independent parameters for multiple regression are the social and environmental ethical values and choices of the people and the dependent parameter is the individual’s propensity to default financially. This conceptual idea stems from the established Social Credit Score concept which is widely used in China and recently been adopted by USA successfully. Based on the interpretation of the data, in the outcomes, if the regression value inclines to be on the higher, then this concept of social credit score based on the intentions and circumstances of the individual can be fetched and companies can use this to predict whether a person will likely default financially. This will provide alternate techniques to companies to predict whether an individual is likely to default financially, apart from the usual CIBIL score which is based mainly on the financial background of the individual. This will help the credit providing companies to bring down the excessive NPAs under control by utilizing this social credit score as an additional parameter before providing credits. Keywords: Credit Rating, Default Financially, Delinquency, Loan, Repayment, Social Credit Score.